Kennedy v. Nixon : The Presidential Election of 1960 - Kallina, Edmund F. (Book collections on Project MUSE., 2006)
This analysis of the movement between 1945 and 1960 substantiates a new but now dominant interpretation of civil rights history that sees grassroots action as the powerful engine that drove racial change. It emphasizes the major role played by women in the cause and documents the variety of civil rights experiences of Jews who migrated to Miami in large numbers during the mid-century decades. Committed to social justice, they built activist organizations, challenged segregationists and anti-Semites, and worked with black activists to break down Jim Crow barriers.